PROBLEMS OF IDENTIFICATION AND THE FORMATION OF TOURIST-RECREATIONAL CLUSTERS - Irina V. Novikova (Вестник Северо-Кавказского федерального университета)
The essence of tourism and recreation cluster. We analyze the algorithm and the method of identification of tourist and recreational clusters in the region. On the example of the Stavropol region shows the use of the author's technique, the essence of which is the use of an integrated economic and cultural-historical approach. The economic approach is based on the positioning of the towns and districts of the region through the use of indicators of the economic, tourist, demographic and other potentials. Cultural-historical approach is to inventory the tourist resources of the area in groups.